Gulf Women and Anti-European Imperialism: Forgotten Gender Discourses in Interwar Iran's Shi'i Reformation Movement - Moslehzadeh, Fatemeh; Blumi, Isa (Middle East critique, 2025)
Often treated as simply anti-modernism, a focus on three reformist figures with transnational intellectual ties-Shariat Sangelaji, Asadollah Kharaqani, and Muhammad Khalesizadeh-reveals how Iranian natives of the Gulf littoral contributed to reconstitute modern life by criticizing the global structures of power arising with European imperialism. Blurring the dichotomy of modern/traditional, Iran and the West, these intellectuals with trans-regional scholarly connections combined different aspects of modernity with a reading of Islamic practice to offer a global model of resistance for Muslims. A version of this Shi'i empowerment in the face of growing changes in the larger world and at home mobilized discussions about women in Iran as the source of the necessary social cohesion during the anti-imperialist struggle. A challenge to normative portrayals of Islam (and religion more generally) as an impediment to progress, studying these three Gulf scholars' alternative modernity allows for identifying a campaign to free women from the consequences of their economic exploitation.